PALLIATIVE CARE FOR PATIENTS WITH ADVANCED HEART DISEASE: A RANDOMISED TRIAL OF EARLY VERSUS DELAYED INTERVENTION. Issue 1 (1st March 2014) - Highet, G; Reid, J; Cudmore, S; Robertson, S; Hogg, K; Murray, S; Boyd, K; Denvir, MA
Abstract : Introduction: Patients with advanced heart disease have a poor prognosis despite optimal disease-focused therapy, and rarely receive coordinated holistic assessment and care planning. Aim(s) and method(s): This project integrated professional and users' views into designing a complex intervention for people with advanced heart disease. The trial combines holistic needs assessment initiated by cardiology specialists with anticipatory care planning and nurse-led care coordination in the community. In the development phase, baseline interviews with healthcare professionals (11) and 2 focus groups comprising 12 patients and 5 carers were conducted. Data were transcribed and analysed for key themes important to the rationale and design of the proposed trial. Participants refined an established, patient-held "Future Care Plan". Recommendations about integration into routine practice informed the final study design. Results: Patients and carers highlighted fragmentation of services, difficulty accessing specialist care and inadequate time and opportunities for future planning. Inclusion of a generic patient-held plan with prompts about current and future priorities offered as part of ongoing support from key professionals was welcomed. Professionals highlighted challenges related to uncertainty of prognosis, explaining mortality-risk to patients, starting to introduce palliative care goals and continuity of care within and across settings. They endorsed patient selection based on prognostic and clinical indicators combined with specialist-initiated care planning continued in primary care and linked to existing patient record systems. Conclusion(s): A diverse group of patients, carers and healthcare professionals identified specific concerns about improving care for people with advanced heart disease and continue to inform a feasible, responsive randomised trial that is now recruiting patients.